The Effect of Technology Adoption on Operational Efficiency of Nepalese Commercial Banks - Gurung, Prabita (Nepalese Journal of Finance, 2024)
This study examines the effect of technology adoption on operational efficiency of Nepalese commercial banks. Operational efficiency is the dependent variables. The independent variables are ATM banking, internet banking, e-payment technology, internet banking, POS banking and mobile banking. The primary source of data is used to assess the opinions of respondents regarding ATM banking, internet banking, e-payment technology, internet banking, POS banking and mobile banking in Nepalese commercial banks. The study is based on the primary data of 132 respondents from the customers of Nepalese commercial banks. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the effect of technology adoption on operational efficiency of Nepalese commercial banks.The study showed that ATM banking has a positive impact on operational efficiency of banks. It indicates that increase in ATM banking services leads to increase in operational efficiency of banks. Similarly, internet banking has a positive impact on operational efficiency of banks. It means that better internet banking leads to increase in operational efficiency of banks. Likewise, e-payment technology has a positive impact on operational efficiency of bank. It means that better e-payment technology services leads to increase in operational efficiency of bank. Likewise, point of sale has a positive impact on operational efficiency of bank. It indicates that increase in point of sale services in retail stores leads to increase in operational efficiency of banks. Similarly, mobile banking has a positive impact on operational efficiency of banks. It means that better mobile banking service leads to increase in the operational efficiency of banks.